Future shift for "big things": From starchitecture via agritecture to parkitecture - Philip Cooke (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This article analyses three recent shifts in what called the geography of "Big Things", meaning the contemporary functions and adaptability of modern city centre architecture. We periodise the three styles conventionally into the fashionable "Starchitecture" of the 1990s, the repurposed "Agritecture" of the 2000s and the parodising "Parkitecture" of the 2010s. Starchitecture was the form of new architecture coinciding with the rise of neo-liberalism in its brief era of global urban competitiveness prevalent in the 1990s. After the Great Financial Crash of 2007–2008, the market for high-rise emblems of iconic, thrusting, skyscrapers and giant downtown and suburban shopping malls waned and online shopping and working from home destroyed the main rental values of the CBD. In some illustrious cases, 'Agritecture' caused re-purposed office blocks and other CBD accompaniments to be re-purposed as settings for high-rise urban farming, especially aquaponics and hydroponic horticulture. Now, COVID-19 has further undermined traditional CBD property markets, causing some administrations to decide to bulldoze their "deadmalls" and replace them with urban prairie landscapes, inviting the designation "Parkitecture" for the bucolic results. This paper presents an account of these transitions with reference to questions raised by urban cultural scholars such as Jane M. Jacobs and Jean Gottmann to figure out answers in time and space to questions their work poses.
Keywords: 650; Agritecture; Big Things; city centre architecture; Parkitecture; Starchitecture